Analysis of Domestic Research Status of Huangjiu Based on Literature Measurement - Yunxia WU; Jingzhang GENG; Zhinan WANG; Runqing LU; Dongqin LI; Fang ZHOU; Honglei TIAN (Shipin gongye ke-ji, 2022)
Objective: As a kind of brewed wine with low alcohol content, rich nutrients and health-care function, huangjiu had a broad development prospect. Mastering the research status and future development trend of huangjiu could provide ideas for the future development of huangjiu industry and in-depth analysis of huangjiu. Methods: The CNKI database was used as the literature source, and the literature metrology method was used to retrieve and analyze the rice wine literature from the aspects of age, distribution of core journals, main authors, and patents. Results: A total of 2953 Chinese and English literature reports and 2643 patents concerning huangjiu research from 1980 to 2021 were retrieved. Conclusion: The analysis showed that the domestic research on huangjiu started late and developed rapidly. The overall volume of articles and patents showed an upward trend. The analysis from the institutions issuing the document, region and other aspects indicated that the research strength of Chinese rice wine was not balanced. The research on huangjiu in China has been diversified from “Shaoxing Huangjiu” to “process” and “fermentation”, and the research topics have been deepened gradually from simple determination of functional components to exploration of functional and active mechanism. The number of patent applications for huangjiu showed a rapid growth trend, and the research direction tended to be diversified. The literature amount of huangjiu and the research status of patent application were analyzed, and the development trend of huangjiu was summarized, which provided reference for the healthy development of huangjiu industry in the future.